1. Limited time only! Sign up for a free 30min personal tutor trial with Chegg Tutors
    Dismiss Notice
Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Help with capital sigma notation please.

  1. Jun 25, 2012 #1
    I was playing a bit with the Riemann Zeta function, and have been struggling with some notation problems.

    The function is defined as follows

    [tex] \zeta (s) = \sum_{n=1}^{\infty} \frac{1}{n^s} [/tex]

    where [tex] s \in \mathbb{C} [/tex]

    we know that

    [tex] n^s = exp(s\;ln\;n)[/tex]

    so I can write

    [tex] \zeta (s) = \sum_{n=1}^{\infty} \frac{1}{exp(s\;ln\;n)} [/tex]

    but since

    [tex] \frac{1}{exp(s\;ln\;n)} = 1 + \frac{1!}{(s\;ln\;n)} + \frac{2!}{(s\;ln\;n)^2} + ... =
    1 + \sum_{n=1}^{\infty} \frac{n!}{(s\;ln\;n)^n} [/tex]

    how can I write this ''sum within a sum''? ζ(s) here, if I am correct, would be an infinite sum of terms which are infinite sums.

    Thank you for taking the time to help!

    edit :

    Could I say

    [tex]1 + \sum_{n=1}^{\infty} \frac{n!}{(s\;ln\;n)^n} = a_k[/tex]


    [tex] \zeta (s) = \sum_{k=1}^{\infty} a_k[/tex]

    Does that make any sense?
  2. jcsd
  3. Jun 25, 2012 #2

    D H

    User Avatar
    Staff Emeritus
    Science Advisor


    What you can say is that
    [tex]\exp (s \ln n) = \sum_{r=0}^{\infty} \frac{(s\ln n)^r}{r!}[/tex]
    What you did, simply inverting each term on the right hand side to get [itex]1/\exp(s\ln n)[/itex], is invalid.

    This is what you need to use for [itex]1/\exp(s\ln n)[/itex]:
    [tex]\frac 1{\exp(s\ln n)} = \exp (-s \ln n) =
    \sum_{r=0}^{\infty} \frac{(-s\ln n)^r}{r!} =
    \sum_{r=0}^{\infty} \frac{(-1)^r(s\ln n)^r}{r!}[/tex]
  4. Jun 25, 2012 #3

    This only makes sense for [itex]\,Re(s)>1\,[/itex]...careful!


  5. Jun 25, 2012 #4
    Thank you DH for the help, and DonAntonio for your rigor, I need to work on that.

    But in this part,

    [tex]\sum_{r=0}^{\infty} \frac{(-1)^r(s\ln n)^r}{r!}[/tex]

    Don't we need to to take the sum of all terms with both n and r, from 1 to ∞? Could I write it as

    [tex]\sum_{n=1}^{\infty} \; \sum_{r=0}^{\infty} \frac{(-1)^r(s\ln n)^r}{r!} [/tex] ??
    Last edited: Jun 25, 2012
Share this great discussion with others via Reddit, Google+, Twitter, or Facebook